ERRADICAÇÃO DA ESCRAVIDÃO MODERNA NO BRASIL: A DIFICULDADE DE EFETIVAÇÃO DO OBJETIVO DE DESENVOLVIMENTO SUSTENTÁVEL (ODS) NÚMERO 8.7 DA AGENDA 2030 - Bruna Nubiato Oliveira (2022)
The dissertation aims to investigate the difficulty of implementing the Sustainable Development Goal (SDG) number 8.7 of the 2030 Agenda in Brazil. Modern slavery is the problem studied, with a view to building possible paths for its eradication. The coexistence of poverty, inequality and modern slavery inhibits the progress of sustainable development. The research is based on studies on human rights and international human rights law. Therefore, poverty is analyzed as a promoter of modern slavery together with inequalities. We understand the right to development, analyzing human capacities for the promotion and effectiveness of sustainable development. It presents analyses of the 2030 Agenda and its developments, as well as a more specific analysis of the target 8.7 of the 2030 Agenda. To achieve the expected objectives, the study uses exploratory and descriptive, bibliographic and documentary research through the analysis of international works, articles, declarations and conventions. The method of approach is deductive, starting from generic concepts until its particularization.